Genome-Wide Association Mapping of Mixed Linkage (1,3;1,4)-β-Glucan and Starch Contents in Rice Whole Grain - Panahabadi, Rahele; Ahmadikhah, Asadollah; McKee, Lauren S.; Ingvarsson, Pär K.; Farrokhi, Naser (Frontiers in Plant Science, 2021)
The glucan content of rice is a key factor defining its nutritional and economic value. Starch and its derivatives have many industrial applications such as in fuel and materials production. Non-starch glucans such as (1,3;1,4)-β-D-glucan (mixed-linkage β-glucan, MLG) have many benefits in human health, including lowering cholesterol, boosting the immune system, and modulating the gut microbiome. In the present study, the genetic variability of MLG and starch contents were analyzed in rice (Oryza sativa L.) whole grain, by performing a new quantitative analyses of the polysaccharide content of rice grains. The 197 rice accessions investigated had an average MLG content of 252 µg/mg, which was negatively correlated with grain starch content. A new genome-wide association study (GWAS) revealed 7 significant quantitative trait loci (QTLs) associated with MLG content, and 2 QTLs associated with starch content in rice whole grain. Novel genes identified as being associated with MLG content were a hexose transporter and anthocyanidin 5,3-O-glucosyltransferase. Also, the novel gene associated with starch content was a nodulin-like domain. Our data pave the way towards a better understanding of the genes involved in determining the content of both MLG and starch contents in rice grains, and should facilitate future plant breeding programmes.